1990
DOI: 10.1177/014920639001600306
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Self-Monitoring and Gender on Leader Emergence: A Laboratory and Field Study

Abstract: Two studies were conducted to investigate the influence of self-monitoring ability and gender on leader emergence. In Study I, groups composed of a male high self-monitor, male low self-monitor, female high self-monitor, andfemale low self-monitor worked on a salary allocation task. At the end of the task, subjects completed questionnaires that asked them to select one group member as their leader. The amount of influence each group member exerted during the discussion was also assessed. Analyses indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2
4

Year Published

1998
1998
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(75 citation statements)
references
References 17 publications
5
64
2
4
Order By: Relevance
“…This result was consistent with previous evidence that high quality of communication is associated with high-level mentalizing (21), which was partly subserved by the left TPJ. Specifically, previous evidence has shown that interpersonal coordination or communication is facilitated by the mutual abilities to predict each other's subsequent action (i.e., high-level mentalizing) (30).…”
Section: Discussionsupporting
confidence: 93%
“…This result was consistent with previous evidence that high quality of communication is associated with high-level mentalizing (21), which was partly subserved by the left TPJ. Specifically, previous evidence has shown that interpersonal coordination or communication is facilitated by the mutual abilities to predict each other's subsequent action (i.e., high-level mentalizing) (30).…”
Section: Discussionsupporting
confidence: 93%
“…Meaning, the extent to which individuals regulate their thoughts and behaviors should be related to the extent to which individuals are monitoring their appearances of self in social settings (Premeaux & Bedeian, 2003;Tsui & Ashford, 1994). Indeed, there is evidence that high self-monitoring employees are adept at interpreting such cues and regulating their selfpresentation accordingly (Dobbins, Long, Dedrick, & Clemons, 1990).…”
Section: Self-regulation Theorymentioning
confidence: 99%
“…Self-monitoring is imperative in informing TSL strategies because, while "self-monitoring may occur in response to internal or external prompts," (Kanfer & Ackerman, 1989; p. 662), high self-monitoring employees place a greater emphasis on situational factors in determining appropriate behaviors (Dobbins et al, 1990). In doing so, these employees gain self-insights by identifying modifiable aspects of their current environment and altering their own behaviors in order to "set in motion a process of corrective change" (Bandura, 1991;p.…”
Section: Self-monitoring and Thought Self-leadershipmentioning
confidence: 99%
“…'Low self-monitors' are less socially sensitive, and either do not possess the ability and/or the motivation to manage how they come across to others. Some evidence suggests that high self-monitors emerge more often as leaders and as people upon whom others depend more than do low self-monitors (Dobbins et al, 1990). Sustained and effective leader-follower relationships are built upon trust.…”
Section: The Perils Of Pollyannamentioning
confidence: 99%
“…Sustained and effective leader-follower relationships are built upon trust. There is also evidence that high self-monitors exert more social (interpersonal) influence and initiate more structure which regulates the behavior of others than their low-self-monitoring counterparts (Dobbins et al, 1990). Consequently, there are at least three mechanisms by which high self-monitors can produce false trustworthiness -they are able to manage (and potentially distort) others' perceptions of themselves, they are able to manage relationships to create dependencies, and they are able to exert the social influence that creates trusting behavior.…”
Section: The Perils Of Pollyannamentioning
confidence: 99%